2012
DOI: 10.2214/ajr.11.7029
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Combined Noninvasive Anatomic and Functional Assessment With Dual-Source CT and Adenosine-Induced Stress Dual-Energy CT for Detection of Significant Coronary Stenosis

Abstract: Combined dual-source coronary CTA and CT MPI provides incremental diagnostic value compared with dual-source coronary CTA alone for the detection of significant coronary stenoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 33 publications
2
49
1
4
Order By: Relevance
“…Different vendors have re-introduced DECT and in recent years the technique has become clinically feasible. The DECT acquisition may be performed using a DSCT with two tubes simultaneously emitting higher (140-150 kV) and lower (80-90-100 kV) energy levels (35)(36)(37). A second approach consists of a single-source CT scanner with rapid kV switching (from 80 to 140 kV) to acquire the dualenergy samples almost simultaneously either in a single gantry rotation (GSI Cardiac; GE Healthcare), or in consecutive rotations (Acquilion One; Toshiba) (12,16,34).…”
Section: Static Ctp Imaging-dual-energy Ct Acquisitionmentioning
confidence: 99%
“…Different vendors have re-introduced DECT and in recent years the technique has become clinically feasible. The DECT acquisition may be performed using a DSCT with two tubes simultaneously emitting higher (140-150 kV) and lower (80-90-100 kV) energy levels (35)(36)(37). A second approach consists of a single-source CT scanner with rapid kV switching (from 80 to 140 kV) to acquire the dualenergy samples almost simultaneously either in a single gantry rotation (GSI Cardiac; GE Healthcare), or in consecutive rotations (Acquilion One; Toshiba) (12,16,34).…”
Section: Static Ctp Imaging-dual-energy Ct Acquisitionmentioning
confidence: 99%
“…In two studies in 45 and 35 angina patients, respectively, MPI-CT combined with CTCA had a PPV of 88 % and 86 % and an NPV of 91 % and 93 %, respectively, in a per-vessel analysis for the detection of≄ 50 % stenosis on ICA [48,49]. In 42 patients with at least 1≄50 % angiographic stenosis on ICA, MPI-CT combined with CTCA was compared with invasive FFR by Ko et al [50].…”
Section: Combining Anatomy and Functionmentioning
confidence: 99%
“…Diagnostic accuracy was found to be comparable to that of SPECT. Ko et al 93 reported increases in sensitivity, specificity, PPV, and NPV from 91.8%, 67.7%, 73.6% and 87.5% to 93.2%, 85.5%, 88.3% and 91.4%, respectively, by adding DE FP CT to DE CTA (Figure 4). …”
mentioning
confidence: 98%